The elements of negotiation the 103 tactics for everyone to win in each deal - Jensen, Keld (Ascent Audio, 2024)
The Elements of Negotiation provides listeners with an easy-to-follow step-by-step approach to becoming exceptional negotiators in both their professional and personal lives. Grounded in twenty-four years of extensive research, studying the habits and techniques of 35,000 individual negotiators, the 103 steps provide a detailed roadmap for negotiation excellence, covering preparation, execution, and post-negotiation analysis. Backed by tested science proving the tips' efficacy, The Elements of Negotiation explores a wealth of real-world case studies and examples, with trends and predictions into the future of negotiation, and additional resources and training programs to further improve your negotiation skills.
Online resource; title from title details screen (O'Reilly, viewed October 22, 2024)
Keywords: Negotiation in business; Negotiation; Interpersonal relations; Négociations (Affaires); Négociations; Audiobooks; Livres audio